Asymmetric Transfer Hydrogenation of Trifluoromethylated Imines to Chiral α‐Trifluoromethylated Amines With Alcohol as The Hydrogen Source. Issue 6 (19th May 2021) - Wang, Zheting; Yang, Chunhui; Chen, Jingchao; Yang, Fan; Khan, Ruhima; Yang, Yong; Qiao, Xingfang; Su, Zhimin; Fan, Baomin
Abstract: An efficient Pd/Zn co‐catalyzed method for the asymmetric transfer hydrogenation of trifluoromethylated imines to chiral α ‐trifluoromethylated amines using methanol as the hydrogen source has been developed. The reaction showed good substrate scope and the products were obtained in excellent yields (up to 99%) with excellent enantioselectivity. The present methodology was compatible for the synthesis of deuterated chiral α ‐trifluoromethylated amines. On using CD3 OD as the deuterium source, deuterium incorporation up to 98% was observed without compromising the reaction outcome. Abstract : A new method for the synthesis of the important chiral α ‐trifluoromethylated amine scaffold was developed . The reaction proceeded by the asymmetric transfer hydrogenation of α ‐trifluoromethylated imines with methanol as hydrogen source under the Pd/Zn co‐catalysis. The products were obtained in high yields (up to 99%) with excellent enantioselectivity (up to 96% ee ). Deuterium incorporation up to 98% was observed when CD3 OD was used.